Study on the Capability of a Two Phase Natural Convection System for Hot-swappable Communication Cabinets - Zhou Jinpeng; Huang Zhencheng; Wang Zhixin; Tong Guinian; Diao Xianghong; Sun Xihui; He Zhenhui (Zhileng xuebao)
Based on the two phase natural convection, a system with R22 for the hot-swappable communication cabinet is built and tested for its heat dissipation capability. The result shows that this system can handle more than 3000W with the cooling water at about 28℃, meanwhile, it keeps the temperature of the electronic module to be lower than 65℃. Moreover, the tests of unbalance heat load start up and varying during operation are carried out to simulate cases of the heat load changing and hot swapping in a real cabinet. The result tells that the system operates stable with unbalance heat load and meets the requirement for hot swapping.